2020
DOI: 10.1101/2020.07.11.198663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed control of motor circuits for backward walking inDrosophila

Abstract: How do descending inputs from the brain control leg motor circuits to change the way an animal walks? Conceptually, descending neurons are thought to function either as command-type neurons, in which a single type of descending neuron exerts a high-level control to elicit a coordinated change in motor output, or through a more distributed population coding mechanism, whereby a group of neurons, each with local effects, act in combination to elicit a global motor response. The Drosophila Moonwalker Descending N… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…During walking, 2D tracking of the tarsal claws traced out stereotypical trajectories in the x-y plane (Figure 3D, top) [50] which corresponded to circular movements in the unmeasured x-z plane (Figure 3D, bottom). These predicted x-z cycles were of largest amplitude for the front, prothoracic legs, consistent with real kinematic measurements during forward walking[51].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…During walking, 2D tracking of the tarsal claws traced out stereotypical trajectories in the x-y plane (Figure 3D, top) [50] which corresponded to circular movements in the unmeasured x-z plane (Figure 3D, bottom). These predicted x-z cycles were of largest amplitude for the front, prothoracic legs, consistent with real kinematic measurements during forward walking[51].…”
supporting
confidence: 85%
“…Remarkably, we found that the network could predict physiologically realistic 3D poses in this new dataset using only ventral 2D poses ( Figure 3G and Video 8 ). During walking, 2D tracking of the tarsal claws traced out stereotypical trajectories in the x-y plane ( Figure 3H , top) [54] and circular movements in the unmeasured x-z plane ( Figure 3H , bottom) whose amplitudes were consistent with real kinematic measurements during forward walking [55].…”
Section: Resultsmentioning
confidence: 79%
“…DNg and DNa01 are in circuits targeted only by the PFL3 neurons and not PFL2 neurons. PFL2 and PFL3 neurons also reach the moonwalker neuron MDN (Bidaye et al, 2014;Feng et al, 2020), which has a bilateral innervation pattern and is known to drive backward walking. This connection is almost exclusively contralateral (Figure 63-figure supplement 1A,B), a suggestion that the MDN could also be involved in asymmetric behaviors.…”
Section: Cre and Smp Connections To Mbons And Dansmentioning
confidence: 99%
“…This high-level, overarching, CPG can control the alternations between leg rubs and sweeps that are themselves governed by faster, low-level CPGs. The idea that multiple CPGs coordinate movements is not new: CPGs may control each leg joint, regulating the interaction between flexor and extensor muscles, governing the way coxa-trochanter and femur-tibia joints are coordinated to produce forward or backward walking, or mediating interactions among limbs (Feng et al, 2020;Mantziaris, Bockemuhl, & Buschges, 2020). In the vertebrate spinal cord, inhibitory and excitatory commissural neurons can cause the CPGs controlling the legs to synchronize for a hopping gait or operate out-of-phase for walking (Kiehn, 2016).…”
Section: Discussionmentioning
confidence: 99%